Lithium Battery Ingestion: An Unusual Cause of Bilateral Cord Palsy - Gautam Bir Singh; Ravinder Chauhan; Deepak Kumar; Rubeena Arora; Shruti Ranjan (Case Reports in Otolaryngology)
Bilateral vocal cord palsy is a rare but life threatening complication of lithium battery ingestion in children. This complication is mostly missed by otorhinolaryngologists due to lack of awareness on the cited subject. We present one such rare case in an infant, where the clinical presentation was found to be unique but hitherto unreported in the medical literature. This clinical record discusses this case in light of the scant current medical literature on the subject and highlights the importance of cautious monitoring of patients presenting with signs of respiratory distress after lithium battery removal.